Motorbike taxis in the "transport crisis" of West and Central African cities - Lourdes Diaz Olvera; Didier Plat; Pascal Pochet; Sahabana Maïdadi (EchoGéo)
Motorized two-wheelers have been appropriated for a commercial activity, the motorbike taxi, in a number of Sub-Saharan African cities. The aim of this paper is to determine the conditions which have made it possible for motorized two-wheelers to become a major public transport mode, and to highlight their role in daily travel. The rise of motorbike taxis can be explained by the shortage of transport supply, the availability of factors of production and the permissiveness of the regulatory framework. Motorbike taxis extend access to motorized modes of transport to larger groups of population whose travel needs are not satisfied by the other modes of public transport.